STUDIES OF PHYSICOCHEMICAL PARAMETERS AND ZOOPLANKTON DIVERSITY IN TAKERIAL LAKE OF KAMAREDDY DISTRICT, TELANGANA - KUMAR, P. ANIL; BALAKRISHNA, D.; JANGIR, O. P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
In the present study the Takerial lake is selected for the assessment of various physico chemical parameters and zooplankton diversity. Takerial lake is located 5 km far away from the Kamareddy district head quarter of Telangana state. In this study total fifteen different physico chemical parameters and four major groups of zooplankton were analyzed during the year 2019-2020. The results of physicochemical parameters clearly supports the lake water is useful for various agriculture activities and the water is also suitable for domestic purpose. The observed four groups of zooplankton are Rotifera, Copepoda, Cladocera and Ostracoda. Among all the four group of zooplankton the Rotifera group of zooplankton were dominated and followed by Copepoda, Cladocera and Ostracoda respectively.